Review on Innovative DC-DC Converter Design for High Efficiency and High Voltage Gain Applications - Putra, Andi Muhammad Nur; Adrianti, Adrianti; Hamid, Muhammad Imran (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2025)
This paper reviewed the advancements in DC-DC converter technologies, emphasizing their role in addressing the demands of high efficiency and high voltage gain in renewable energy systems, electric vehicles (EVs), and distributed energy networks. Advanced topologies, including hybrid, quadratic, triple-boost, coupled inductor, and voltage multiplier designs, were evaluated for their ability to overcome the limitations of traditional converters. Key findings highlighted significant improvements in energy efficiency, exceeding 95%, and a substantial reduction in voltage ripple. Performance metrics such as scalability, thermal management, and component stress were analized, demonstrating the suitability of these designs for diverse applications. Comparative analyses illustrate the superiority of innovative designs in meeting the energy needs of emerging technologies. Applications in renewable energy, EV infrastructure, and distributed networks underscore the transformative potential of these converters in optimizing power delivery and enhancing system reliability. This review bridged the gap between theoretical advancements and practical implementations, showcasing the pivotal contribution of DC-DC converter to modern energy systems.